How to Understand What Passes All Understanding: Using the Documentary Papyri to Understand εἰρήνη in Paul. (April 2021) - Dormandy, Michael
Abstract : In popular culture, the Pauline texts referring to 'peace' are illustrated by serene and tranquil scenes. I shall argue that to Paul's first readers, 'peace' evoked rather different images – military victories, arrests of criminals and the unloading of corn. I argue this because of how εἰρήνη is normally used in documentary papyri, that is personal letters, administrative documents and other non-literary written material. I explain my method and then present the papyrological evidence, including references to the various 'peace-officials'. I argue that εἰρήνη meant something like 'good order'. I use this insight to interpret Rom 5.1 and Phil 4.7.